Pedagogical Analysis of the Baroque Period Piano Repertoire: Example of Italy - YÜCETOKER, İZZET (My University, 2021)
The aim of this study is to access editions of Italian Baroque works in place; to examine the availability of these works in terms of gaining techniques for playing in piano education, to gain new works aimed at different pedagogical stages in the field and to acquire new but unknown works in piano education repertoire. This research was carried out with the literature review model. During the first three months of the research, 158 baroque period composers were found among 2173 Italian composers. 50 composers composing on keyboard instruments were reached among 158 baroque composers. For this research study, the library of Dipartimento delle Arti dell’Universita di Bologna the Sala Borsa library, the Giovanni Martini Conservatory library and international museum and library of music in Bologna were visited and the works of composers made on the keyboard instruments were found. The number of works performed by composer on keyboard instruments is quite high. However, according to the objective of the project, it is aimed to perform pedagogical analysis by selecting one work from each composer. For analysis, created to the work evaluation forms prepared by the researcher. 50 works analyzed according to this form. While 48 Italian works can be used in piano education, 6 Italian works are not suitable for piano education. However, in order to use these works in piano education, these must be arranged from organ to pianoforte. An example of this is presented in this study. Keywords: Baroque, Italian Baroque, Italian composers, music education, pianoforte
Keywords: Baroque; Italian Baroque; Italian composers; music education; pianoforte